1987
DOI: 10.1111/j.1365-2222.1987.tb02046.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of grass–maize pollen oral immunotherapy in patients with seasonal hay‐fever: a double‐blind study

Abstract: SummaryForty patients with a well‐documented history of seasonal hay fever and a positive skin‐prick test specific to grass pollen, including Bermuda grass and maize pollen (Zea maize), were allocated randomly on a double‐blind basis to receive either an oral mixed grass–maize pollen extract or a matched placebo during the 1981/1982 grass pollen season. After 12 months the code was broken and patients on placebo were transferred to active therapy while patients on active therapy continued with maintenance ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 5 publications
1
28
0
Order By: Relevance
“…Our retention rate (75%) is good for a community-based study and compares favorably with those of other published 2-year SLIT studies. 14,15 Side effects were reported by many subjects, even those receiving placebo. In part, this reflects the care we took to capture side effects.…”
Section: Discussionmentioning
confidence: 98%
“…Our retention rate (75%) is good for a community-based study and compares favorably with those of other published 2-year SLIT studies. 14,15 Side effects were reported by many subjects, even those receiving placebo. In part, this reflects the care we took to capture side effects.…”
Section: Discussionmentioning
confidence: 98%
“…Scadding and Brostoff described low dosage sublingual therapy in patients with allergic rhinitis due to house dust mite [7]. Van Niekerk and De W et dem onstrated the ef® cacy of grass, maize, pollen oral immunotherapy in patients with seasonal hay fever [8]. The most extensive study of all was perform ed by King et al (1988) and was a two-part m ulti-centre study describing the intracutaneous provocation food test and subcutaneous neutralization therapy [9].…”
Section: Discussionmentioning
confidence: 99%
“…In latter ceremonials maize pollen was placed on or under the tongue, or eaten. Some studies suggested that subjects exposed to maize pollen were prone to develop asthma, allergic rhinitis and/or allergic conjunctivitis [23,25,26]. …”
Section: Discussionmentioning
confidence: 99%